A legal study on regulating the sale of controlled substances through the internet in Malaysia with special reference to the United States of America (USA) / Zurainy A. Samah - A. Samah, Zurainy (2017)
The growing phenomenon of Internet has influenced the way consumers obtain their medications. The easy accessibility and availability of all of medicines in the Internet has raise the concern of illegal sale of controlled substances, which are highly abusive and unregulated sale often used by drug addiction. This research examine the adequacy of the existing laws in governing the sale of controlled substances through the Internet. Using doctrinal approach, this research focuses on the main statutes namely the Poison Act 1952, the Poison Regulation (Psychotropic Substances) 1989 and the Sale of Drug Act 1952. This research also examines the applicability of other statutes that related to Internet. A comparative analysis of statutes which regulate the sale of controlled substances by means of the Internet in the US was carried out to observe their legal framework. In addition to that, a semi-structured interview also was conducted with the respondents from the Pharmacy Enforcement Division (PED). Findings from the interviews as well as through the comparative analysis were utilised to identify the problems, issues and challenges, and proposes for appropriate recommendations. The current laws were found inadequate to govern the sale of controlled substances through the Internet. Thus, through this research it is proposed that the existing law to be amended to accommodate the handling of Internet transaction. This research also proposes some other recommendations such as to develop a mechanism to licence the internet pharmacies and verification of legitimacy of the website.